The complete mitochondrial genome of Lutraria maxima Jonas (Veneroida: Mactridae) - Shengping Zhong; Yanfei Zhao; Xianfeng Wang; Zhifei Song; Qing Zhang (Mitochondrial DNA. Part B. Resources, 2017)
The snout otter clam Lutraria maxima Jonas (Veneroida: Mactridae) is an economically important species in the marine bivalves fishery and aquaculture in China. However, the genetic information of this species remains unavailable. In this study, we report the complete mitochondrial genome sequence of L. maxima. The mitogenome has 17,082 base pairs (63.9% A + T content) and made up of a total of 37 genes (13 protein-coding, 22 transfer RNAs and two ribosomal RNAs), and a 1045 bp non-coding control region. The presence of a gene coding for ATPase subunit 8 was also noted. However, as expected in Mactridae, the gene arrangements showed variations with that of the related species. This study adds to the repository of available mitogenomes of various Mactridae and will provide useful genetic information for future fishery management and aquaculture development of Mactridae.